Effectiveness of Scapular Stabilization Versus Non-Stabilization Stretching on Shoulder Range of Motion, a Randomized Clinical Trial - Alan J Howell; Andrew Burchett; Nicholas Heebner; Cody Walker; Alec Baunach; Asia Seidt; Tim L Uhl (International Journal of Sports Physical Therapy)
# Background